Discovery of novel rhabdoviruses in the blood of healthy individuals from West Africa. - Matthew H Stremlau; Kristian G Andersen; Onikepe A Folarin; Jessica N Grove; Ikponmwonsa Odia; Philomena E Ehiane; Omowunmi Omoniwa; Omigie Omoregie; Pan-Pan Jiang; Nathan L Yozwiak; Christian B Matranga; Xiao Yang; et al. (Public Library of Science (PLoS), 2015)
Next-generation sequencing (NGS) has the potential to transform the discovery of viruses causing unexplained acute febrile illness (UAFI) because it does not depend on culturing the pathogen or a priori knowledge of the pathogen's nucleic acid sequence. More generally, it has the potential to elucidate the complete human virome, including viruses that cause no overt symptoms of disease, but may have unrecognized immunological or developmental consequences. We have used NGS to identify RNA viruses in the blood of 195 patients with UAFI and compared them with those found in 328 apparently healthy (i.e., no overt signs of illness) control individuals, all from communities in southeastern Nigeria. Among UAFI patients, we identified the presence of nucleic acids from several well-characterized pathogenic viruses, such as HIV-1, hepatitis, and Lassa virus. In our cohort of healthy individuals, however, we detected the nucleic acids of two novel rhabdoviruses. These viruses, which we call Ekpoma virus-1 (EKV-1) and Ekpoma virus-2 (EKV-2), are highly divergent, with little identity to each other or other known viruses. The most closely related rhabdoviruses are members of the genus Tibrovirus and Bas-Congo virus (BASV), which was recently identified in an individual with symptoms resembling hemorrhagic fever. Furthermore, by conducting a serosurvey of our study cohort, we find evidence for remarkably high exposure rates to the identified rhabdoviruses. The recent discoveries of novel rhabdoviruses by multiple research groups suggest that human infection with rhabdoviruses might be common. While the prevalence and clinical significance of these viruses are currently unknown, these viruses could have previously unrecognized impacts on human health; further research to understand the immunological and developmental impact of these viruses should be explored. More generally, the identification of similar novel viruses in individuals with and without overt symptoms of disease highlights the need for a broader understanding of the human virome as efforts for viral detection and discovery advance.